Structural and Dielectric Properties of Zn1-xMoxO Nanoparticles - H. Basma; F. Al-Mokdad; R. Awad (Jordan Journal of Physics, 2025)
In this work, samples of zinc oxide nanoparticles doped by molybdenum (Zn1-xMoxO with 0 ≤ x ≤ 0.1) were prepared by using the wet co-precipitation method. The characterization of the prepared samples was carried out by means of X-ray powder diffraction (XRD). The samples reserved their hexagonal wurtzite structure with Mo doping and showed a decrease in the crystallite size up to x = 0.04 followed by a further increase. On the other hand, dielectric measurements were performed using an LCR meter. The effect of frequency and temperature on the dielectric properties such as the real and imaginary parts of dielectric constant ( and , respectively), dielectric loss (tan ) and ac-conductivity ( ) of Mo-doped zinc oxide samples, was studied in the frequency range (100 Hz - 1 MHz) and at temperatures (300 - 773 K). The values of room temperature dielectric parameters were found to be strongly dependent on the Mo-doping. However, the increase in temperature caused an enhancement in the values of the dielectric parameters, particularly at 773 K. Keywords: Zinc oxide, XRD, Dielectric constants, Ac-conductivity.